Acceleration of Bone-Tendon Interface Healing by Low-Intensity Pulsed Ultrasound Is Mediated by Macrophages. Issue 7 (9th February 2021) - Li, Shengcan; Xu, Zihan; Wang, Zhanwen; Xiang, Jie; Zhang, Tao; Lu, Hongbin
Abstract: Objective: Low-intensity pulsed ultrasound (LIPUS) has been proven to facilitate bone-tendon interface (BTI) healing and regulate some inflammatory cytokines. However, the role of macrophages, a key type of inflammatory cell, during treatment remains unknown. This study aimed to investigate the role of macrophages in the treatment of BTI injury with LIPUS in a rotator cuff tear animal model. Methods: In this experimental and comparative study, a total of 160 C57BL/6 mature male mice that underwent supraspinatus tendon detachment and repair were randomly assigned to 4 groups: daily ultrasonic treatment and liposomal clodronate (LIPUS+LC), daily ultrasonic treatment and liposomes (LIPUS), daily mock sonication and liposomal clodronate (LC), and daily mock sonication and liposomes (control [CTL]). LIPUS treatment was initiated immediately postoperatively and continued daily until the end of the experimental period. Results: The failure load and stiffness of the supraspinatus tendon–humerus junction were significantly higher in the LIPUS group than in the other groups at postoperative weeks 2 and 4, whereas those in the LIPUS+LC and LC groups were lower than those in the CTL group at postoperative week 4. The LIPUS, LIPUS+LC, and LC groups exhibited significantly more fibrocartilage than the CTL group at 2 weeks. Only the LIPUS group had more fibrocartilage than the CTL group at 4 weeks. Micro-computed tomography results indicated that LIPUS treatment could improve the bone quality of the attachment site after both 2 and 4 weeks. When macrophages were depleted by LC, the bone quality–promoting effect of LIPUS treatment was significantly reduced. Conclusion: The enhancement of BTI healing by LIPUS might be mediated by macrophages. Impact: In our study, LIPUS treatment appeared to accelerate BTI healing, which was associated with macrophages based on our murine rotator cuff repair model. The expressions of macrophage under LIPUS treatment may offer a potential mechanism to explain BTI healing and the effects of LIPUS on BTI healing.